2020
DOI: 10.1136/bmjopen-2020-036777
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the prevalence and treatment of depressive symptoms in Peru: a population-based study

Abstract: ObjectivesThis study aimed to estimate the trends in the prevalence and treatment of depressive symptoms using nationally representative surveys in Peru from 2014 to 2018.DesignA secondary analysis was conducted using five nationally representative surveys carried out consecutively in the years between 2014 and 2018.SettingThe study was conducted in Peru.ParticipantsIndividuals, men and women, aged ≥15 years who participated in the selected surveys. Sampling was probabilistic using a two-stage approach.Main ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 37 publications
2
30
1
5
Order By: Relevance
“…The PHQ-9 has been utilized in Latin American populations, including in rural areas of Mexico, suggesting that the internal consistency of the PHQ-9 was good overall and in subgroups of low literacy levels, gender, and age (50). The PHQ-9 has also been validated for use in Peru (49), and studies suggest that those of lower socioeconomic status or from rural areas had lower rates of depression (82). One study from Latin America of 412 Brazilian PWH utilized the Beck Depression Inventory (BDI) for depression screening and found that a BDI score between 13 and 19 points was associated with symptomatic HAND (mild neurocognitive disorder and HIV-associated dementia) (16).…”
Section: Neurocognitive Testing Resultsmentioning
confidence: 99%
“…The PHQ-9 has been utilized in Latin American populations, including in rural areas of Mexico, suggesting that the internal consistency of the PHQ-9 was good overall and in subgroups of low literacy levels, gender, and age (50). The PHQ-9 has also been validated for use in Peru (49), and studies suggest that those of lower socioeconomic status or from rural areas had lower rates of depression (82). One study from Latin America of 412 Brazilian PWH utilized the Beck Depression Inventory (BDI) for depression screening and found that a BDI score between 13 and 19 points was associated with symptomatic HAND (mild neurocognitive disorder and HIV-associated dementia) (16).…”
Section: Neurocognitive Testing Resultsmentioning
confidence: 99%
“…Although the pre-pandemic prevalence of depression in Peru is estimated to have been stable and not increasing [36], the national prevalence has likely increased during the pandemic. The increase in the prevalence is especially true for people who are aware of having a chronic disease [37], as they are at-risk populations.…”
Section: Prevalencementioning
confidence: 99%
“…These strategies could prevent the latter individuals from evolving to a more advanced stage involving significant health problems and generating years of life lost due to disability [47]. Third, in Peru and other LMICs, the treatment gap for mental health problems such as depression is high, and it is estimated that only 1 in 10 people who require treatment receive it [36]. This gap may have increased during the pandemic, so actions to increase access to appropriate care need to be targeted.…”
Section: Implications In Public Health and Making Decisionsmentioning
confidence: 99%
“…Contrarily, age, gender, and monthly income did not show signi cant results. Previous studies in Peru showed that women over 75 years old and those belonging to the lowest wealth quintile are more likely to have depressive symptoms 42,43 . If wealth is to be considered alone as a factor in depressive symptoms, it could be said that health professionals would be at a lower risk of developing depressive symptoms.…”
Section: Relationship and Comparisons Between Variablesmentioning
confidence: 93%